The Implementation of Talking Stick Model Assisted by Audio-Visual Media Toward Positive Character and Learning Outcome - Asri, Betty Widya; Nurhalim, Khomsun; Suhandini, Purwadi (Journal of Primary Education, 2019)
This research aims to describe the positive character and learning outcomes of students in Civic Education by using the talking stick model assisted by audio-visual media. The type of research is a mixed method with concurrent embedded research designs. The qualitative data were obtained from are interview, observation, and documentation. The quantitative data were obtained from learning outcome and questionnaire. The quantitative analysis uses proportion test, independent sample t-test, and regression testing. Whereas the qualitative analysis includes data reduction, data display, and conclusion drawing/verification. The results of this research were (1) The positive character of N-gain in the experimental class was 0.65 and the control class was 0.15 The most prominent character in this learning process was the brave attitude because talking stick model stimulate students to express their opinions while the character that was not optimal is responsibility where some students have not yet contributed to their group. (2) There was an increase in learning outcomes, proven that the learning outcomes of N-gain in the experimental class was 0.76 and the control class was 0.49. (3) The implementation of this learning model was 83.3%, students’ responses to every aspect of the questions was more than 75% and the average N-gain of learning outcomes showed that the experimental class was higher than the control class. The conclusion of this research is the application of the Talking Stick model assisted by audio-visual media can improve the positive character and students’ learning outcomes in Civic Education.